KOMPETENSI PESERTA SELEKSI MAHASISWA BERPRESTASI TINGKAT FAKULTAS TAHUN 2017 (Studi Kasus Mapres Di Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau) - Eka Dea Putri; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Universities that are often referred to as miniature countries, always give birth to human resources that are competent and integrity. Resources that have competency and ability are not the only thing created by the mechanism in the room, such as lectures. But it can often be generated through outdoor learning that trains and guides, thus giving rise to the self-development of the prospective scholars in the face of problems. With the implementation of pilmapres at the national level, every university is expected to identify and reward students who are excelling and boast continuously. Therefore, universities are expected to have policies that encourage the development of such activities. The problem of this research is what are the aspects of complications that affect students excel at the Faculty of Social and Political Sciences University of Riau. The purpose of this research is to analyze aspects of the complications that affect students excel at the Faculty of Social and Political Sciences University of Riau. The concept of theory used in this research is the theory of competence by Anies Baswedan, which consists of four aspects that are critical, creative, communicative and collaborative. This research uses qualitative descriptive research methods. In this research researchers use observation techniques and interviews.  The results of this research resulted in the conclusion that there is one aspect that has not been well implemented by the students of achievement, namely the collaborative aspect. Students achievers have not been able to optimally apply their achievements to both interest and creativity in the campus environment well. It was justified by the judges in the selection of outstanding students in 2017.